BIOFEEDBACK IN REEDUCATION PERINEUMSPHINCTER WITH PATIENTS MULTIPLE SCLEROSIS - Martinez-Gonzalez, M; Pelegrin Molina, Ma A; Gdmez-Conesa, A (Cuestiones de Fisioterapia, 2003)
Biofeedback is a technique of behavior therapy. It is based in the employment of generally electric instruments that detect internal physiologic processes and it shows information to people about a physiologic and/or physiologic activity. This instrument let the control or modification of determined functions. This way, the physiologic or pathological state of any function becomes perceptible to the people by means sound and/or visual stimulation that offers the apparatus. Bladder and intestinal disorders are common in patients with multiple sclerosis. Most of them suffer symptoms of bladder dysfunction as well as disorders of the defecation (constipation or faecal incontinence).When the bladder and intestinal problems in multiple sclerosis patients are caused by the alterations of the muscular tone, the electromyographic biofeedback is used because transmit the level of electric activity associated to the muscular contraction to the person. When the motor dysfunction of incontinence is associated with sensitive alterations, the manometric biofeedback is also used to detect and transmits the levels of tension in the walls of the bladder or the rectum, as well as the response of external and internal sphincters when pressure is changed.